A Diamond Nanoneedle Array for Potential High‐Throughput Intracellular Delivery. Issue 8 (August 2013) - Chen, Xianfeng; Zhu, Guangyu; Yang, Yang; Wang, Beilei; Yan, Li; Zhang, Kenneth Yin; Lo, Kenneth Kam‐Wing; Zhang, Wenjun
<x xml:space="preserve">Abstract</x> A dense diamond nanoneedle array is capable of rapidly and conveniently delivering fluorescent probe and drug molecules to a large number of cells. This simple approach paves the way for potential high‐throughput delivery of genes, drugs, and fluorescent probes into cells without endocytosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>